THE DUALISM OF THE SUPREME COURT’S DECISIONS ON THE POSITION OF NON-MARITAL CHILD - Nurhadi Nurhadi (Jurnal Hukum dan Peradilan, 2019)
Since the birth of the Constitutional Court Decision Number 46/PUU-VIII/2010, the legal experts have discussed the positions of marriage children through articles, papers, books and seminars, pros and cons when interpreting the non-marital child, judges also gave birth to many interpretations. The Supreme Court (MA) has two views in adjudicating the marriage case, Supreme Court Decision Number 329 K/AG/2014 states that the ratification of an unmarried child is not a jurisdiction of the Religious Courts, whereas in Decision of Supreme Court Number 597 K/AG/2015 states that the non-marital children are legitimate even though the marriage of their parents only carries out marriage under Islamic law. The formulation of the problem is how the criteria of marital legitimacy in Indonesia? How is the outsider interpretation of the two Supreme Court decisions? The research method used is literature study, with the type of normative legal research, which is descriptive analytical. The conclusion is that in Supreme Court Decision Number 329 K/AG/2014 considered the marriage to be legitimately religious, but because it is not recorded so that the marriage does not get the certainty and protection of the law, consequently the child born from the marriage is not a legal child, whereas in Decision Number 597 K/AG/2015 The Supreme Court considers that although the marriage is not recorded, the child born from the marriage must still have legal certainty and protection so that the child is considered a legal child.